Pengaruh Ukuran Dewan Komisaris, Kepemilikan Asing Dan Profitabilitas Terhadap Kualitas Sustainability Report (Studi Empiris Perusahaan Jasa Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia BEI Tahun 2012 - 2016) - Novia Khairunnisa; Triyani Budyastuti (Jurnal Pena-Mas Akuntansi, 2022)
This research was conducted to examine the effect of board size, foreign ownership and profitability on the quality of sustainability report. The purpose of this study is to find out and analyze the influence of board size, foreign ownership and profitability on the quality of sustainability report. The population in this study were banking companies listed on the Indonesia Stock Exchange in 2012 - 2016. The sampling technique in this study was purposive sampling. Many samples that fit the specified criteria were as many as 6 companies. Based on research shows that simultaneously, this research variable has a significant influence on the sustainability report. While partially foreign ownership has a significant negative effect on the quality of sustainability report. And the size of the board of commissioners and profitability does not have a negative and significant effect on the quality of the sustainability report.